2017
DOI: 10.5897/jat2017.0246
|View full text |Cite
|
Sign up to set email alerts
|

The impact of intellectual capital on the financial performance of listed Nigerian food products companies

Abstract: This study examines the impact of intellectual capital (IC) on financial performance of listed Nigerian food products companies for five year period 2010 to 2014 by adopting Pulic model of IC known as value added intellectual coefficient (VAIC). Regression models are used to test the hypotheses of the study where the results show that there was positive significant influence of IC on financial performance. Specifically, the results showed that structural capital (SC) and capital employed (CE) influence the fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
1
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
4
1
1
2
Order By: Relevance
“…This indicates that Nigerian consumer goods companies' financial performance is anticipated to improve when intellectual capital increases through improvements in human capital, structural capital, and relational capital. This supports the research by Shafiu, Noraza, and Saleh (2017), who found that structural capital significantly and positively affects returns on assets. To put it another way, adding structural capital enhances financial performance, which is attained by giving employees the best technology for the job and sound business plans.…”
Section: Discussion Of Findingssupporting
confidence: 91%
“…This indicates that Nigerian consumer goods companies' financial performance is anticipated to improve when intellectual capital increases through improvements in human capital, structural capital, and relational capital. This supports the research by Shafiu, Noraza, and Saleh (2017), who found that structural capital significantly and positively affects returns on assets. To put it another way, adding structural capital enhances financial performance, which is attained by giving employees the best technology for the job and sound business plans.…”
Section: Discussion Of Findingssupporting
confidence: 91%
“…The study also found that STVA had a positive and significant effect on ROA. The results of this study support stakeholder theory and resource theory, and are in line with Fathi et al (2013), Arslan and Zaman (2015), Kurfi et al (2017), Chowdhury et al (2018) which found that structural capital value added has a positive and significant effect on the company's financial performance. According to stakeholder theory, value creation from company activities will improve company performance.…”
Section: E Discussionsupporting
confidence: 87%
“…It was arrived after carrying out the Hausman specification test which favors fixed effect (P-Value 0.0008). The regression result shows that intellectual capital measures using VAIC have a negative and significant influence on financial performance, this is consistent with the findings of (Nuryaman, 2015) and (Shafi'u et al, 2018) but contrary to the findings of (Ozkan et al, 2017). furthermore, the interaction effect was found to be positive and significant on the relationship between intellectual capital and financial performance of listed conglomerate firms in Nigeria.…”
Section: Resultssupporting
confidence: 79%